1990
DOI: 10.1037/0012-1649.26.1.160
|View full text |Cite
|
Sign up to set email alerts
|

Socialization, perspective-taking, and the sibling relationship.

Abstract: Examined the relations among (a) the quality of the sibling relationship, (b) maternal socialization techniques about infant's emotions and skills, (c) first-born's perspective-taking skills, and (d) firstborn's caretaking behavior in 32 sibling pairs (14 months; 3-5 years) and their mothers, observed both at home and a modified lab, strange situation. First-borns' references to second-boms about feelings and skills were positively associated with perspective-taking and friendly sibling relations during mother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
114
0
8

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(130 citation statements)
references
References 15 publications
(30 reference statements)
8
114
0
8
Order By: Relevance
“…Subsequently, Stewart and Marvin (1984) reported a positive association between sibling caretaking and perspective-taking skills, suggesting that the ability to comfort a distressed younger sibling may be associated with the child's understanding of another's feelings. Although Howe and Ross (1990) failed to replicate this finding, they reported significant positive associations between preschooler perspective-taking, internal state language, and friendly sibling interactions. Garner et al (1994) demonstrated that sibling caretaking in a low SES sample was positively predicted by preschoolers' emotional knowledge and expression of positive emotions in the family; specifically, older females were more likely to care for distressed younger siblings and were more knowledgeable about caretaking scripts.…”
Section: Family Experiences As a Context For Social Understanding: Thmentioning
confidence: 47%
See 2 more Smart Citations
“…Subsequently, Stewart and Marvin (1984) reported a positive association between sibling caretaking and perspective-taking skills, suggesting that the ability to comfort a distressed younger sibling may be associated with the child's understanding of another's feelings. Although Howe and Ross (1990) failed to replicate this finding, they reported significant positive associations between preschooler perspective-taking, internal state language, and friendly sibling interactions. Garner et al (1994) demonstrated that sibling caretaking in a low SES sample was positively predicted by preschoolers' emotional knowledge and expression of positive emotions in the family; specifically, older females were more likely to care for distressed younger siblings and were more knowledgeable about caretaking scripts.…”
Section: Family Experiences As a Context For Social Understanding: Thmentioning
confidence: 47%
“…Dunn et al, 1991b), which has also been positively associated with children's social understanding (e.g. Dunn et al, 1991a;Howe and Ross, 1990;Howe, 1991). Although some studies have examined only mental state (e.g.…”
Section: The Role Of Mothers In Family Discourse About Internal Statesmentioning
confidence: 97%
See 1 more Smart Citation
“…Researchers have found links between preschool children's emotional understanding and their mothers' expressions of emotion, as well as their mothers' positive and negative responses to the children's own expressions of emotion (Denham, Zoller, & Couchoud 1994). In addition, the frequency with which mothers discuss emotions (and causality) with children has been linked with children's subsequent use of emotional language and their subsequent levels of emotional understanding (Brown & Dunn, 1996;Denham & Auerbach, 1995;Dunn, Brown, & Beardsall, 1991;Howe, 1990). Thus, whether mothers choose to discuss emotion during conflict, openly express emotion during conflict, and respond to their children's expression of emotion during conflict, likely impacts children's subsequent development of emotional understanding.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have recently argued that these effects largely depend on the quality of the relationship (Lockwood, Kitzmann, & Cohen, 2001) and on the way that siblings judge their relationship (Stormshack, Bellanti, & Bierman, 1996;Woolfe, Want, & Siegal, 2003). That is, those children who have a positive relationship with their sibling show greater understanding of other people's feelings and beliefs (Dunn, Brown, Slomkowski, Tesla, & Youngblade, 1991;Howe & Ross, 1990) and higher social adjustment Updegraff, McHale, & Crouter, 2002). By contrast, a conflictual sibling relationship seems to foster aggressive behaviour (Garcia, Shaw, Winslow, & Yaggi, 2000).…”
mentioning
confidence: 99%